Benjamin’s Girl - Along came a Strawberry - Birdsey, Bianca; Storbeck, Claudine (ABC Press, 2017)
Along came a Strawberry' captures a special evening in the life of Ben and his girl. This little story about fear and courage can be used to unwrap meaningful conversations with young readers. This book provides further opportunity to explore literacy development, language, Theory of Mind and the gift of developing the skill of self-reflection and empathy.
E Book - epub format
Keywords: deaf; studies; roots; teaching